Body Maps of Moral Concerns - Atari, Mohammad; Mostafazadeh Davani, Aida; Dehghani, Morteza (Psychological Science, 2020)
It has been proposed that somatosensory reaction to varied social circumstances results in feelings (i.e., conscious emotional experiences). Here, we present two preregistered studies in which we examined the topographical maps of somatosensory reactions associated with violations of different moral concerns. Specifically, participants in Study 1 ( N = 596) were randomly assigned to respond to scenarios involving various moral violations and were asked to draw key aspects of their subjective somatosensory experience on two 48,954-pixel silhouettes. Our results show that body patterns corresponding to different moral violations are felt in different regions of the body depending on whether individuals are classified as liberals or conservatives. We also investigated how individual differences in moral concerns relate to body maps of moral violations. Finally, we used natural-language processing to predict activation in body parts on the basis of the semantic representation of textual stimuli. We replicated these findings in a nationally representative sample in Study 2 ( N = 300). Overall, our findings shed light on the complex relationships between moral processes and somatosensory experiences.